Field reports form for submitting seasonal observations of Iowa birds, Beth Proescholdt, spring 1983 - Proescholdt, Bethet al (1983)
Spring report of birds and locations contributed by Beth Proescholdt. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1983. Epson - sheet feed